2016
DOI: 10.1063/1.4948304
|View full text |Cite
|
Sign up to set email alerts
|

Low-relaxation spin waves in laser-molecular-beam epitaxy grown nanosized yttrium iron garnet films

Abstract: Synthesis of nanosized yttrium iron garnet (Y3Fe5O12, YIG) films followed by the study of ferromagnetic resonance (FMR) and spin wave propagation in these films is reported. The YIG films were grown on gadolinium gallium garnet substrates by laser molecular beam epitaxy. It has been shown that spin waves propagating in YIG deposited at 700 °C have low damping. At the frequency of 3.29 GHz, the spin-wave damping parameter is less than 3.6 × 10−5. Magnetic inhomogeneities of the YIG films give the main contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 23 publications
1
22
0
1
Order By: Relevance
“…The value of d can be extracted from the period of the fringes, yielding 93, 104, and 115 nm for the YIG thickness on GGG, SGGG, and NGG, and 5.19 ± 0.3, 5.07 ± 0.3, and 5.13 ± 0.6 g cm −3 for the YIG density, respectively. The roughness R a was well below 1 nm, i.e., much smaller than the lattice parameter, but could potentially be further improved by high-temperature annealing before film deposition, as proposed by Lutsev et al [34] The as-grown YIG films are therefore epitaxially strained to match the in-plane lattice parameter of the substrate and have smooth surfaces. [33] Figure 1e shows topographic AFM images of each film.…”
Section: Wwwadvelectronicmatdementioning
confidence: 97%
See 1 more Smart Citation
“…The value of d can be extracted from the period of the fringes, yielding 93, 104, and 115 nm for the YIG thickness on GGG, SGGG, and NGG, and 5.19 ± 0.3, 5.07 ± 0.3, and 5.13 ± 0.6 g cm −3 for the YIG density, respectively. The roughness R a was well below 1 nm, i.e., much smaller than the lattice parameter, but could potentially be further improved by high-temperature annealing before film deposition, as proposed by Lutsev et al [34] The as-grown YIG films are therefore epitaxially strained to match the in-plane lattice parameter of the substrate and have smooth surfaces. [33] Figure 1e shows topographic AFM images of each film.…”
Section: Wwwadvelectronicmatdementioning
confidence: 97%
“…[14,[37][38][39][40][41] The higher value for SGGG/YIG is evidently not a roughness effect since its roughness was similar to that of other samples. [14,34,43] This may arise from magnetic inhomogeneity [34] or the effect of strain and would be improved by the recrystallization of YIG using a post annealing process. [42] In addition, damping parameters were determined independently using the FV SW attenuation length.…”
Section: Damping Parameter Estimationmentioning
confidence: 99%
“…The smallest wavelength λ that we excited by the conventional CPWs amounted to 310 nm. This value is smaller than the wavelengths so far excited via microwave antenna in thin YIG with thicknesses ranging from 20 to 500 nm 3,6,16 . At the same time, we observe modes of higher order compared to earlier publications reporting spin-wave excitation in thin YIG 3,16,21 and thin ferromagnetic metals 22,23 using bare CPWs.…”
mentioning
confidence: 75%
“…The extracted decay length l d amounted to 0.86 mm. Small λ, high v g and large l d are key figures of merit when aiming at non-charged based signal transmission and logic devices with spin waves.Thin films of the insulating ferrimagnet yttrium iron garnet (YIG) have recently shown to exhibit small spin-wave (SW) damping [1][2][3][4][5][6][7] . A large decay length of up to 0.58 mm was reported for SWs in a 20 nm thick YIG film 3 .…”
mentioning
confidence: 99%
“…This research has been restricted, however, to bends composed of metallic films, such as Permalloy. Insulating magnetic materials, such as yttrium iron garnet (YIG), possess significantly smaller magnetic damping compared to magnetic metals, and it has been recently demonstrated that this small damping persists even when the thickness of YIG is reduced to tens of nanometers [23,24]. This suggests a possibility of using irregular YIG magnonic waveguides within all-magnonic insulator-based technology.…”
mentioning
confidence: 99%